Evaluating quality of life in mercury intoxicated people in urban-industrial environments through short-form 36 application - Boscolo Del Vecchio, Fabrício; Gonçalves, Aguinaldo; Padovani, Carlos Roberto [UNESP]; De Araújo Medrado Faria, Marcília; Vilarta, Roberto (My University, 2006)
Context and objective: Records of contact with mercury (Hg) exist for more than 3500 years and several problems related to the use of this element can be noticed. Considering inexistence of current reports about it, quality of life perception evaluation was studied in people chronically intoxicated by mercury in an industrial environment. Design and setting: This is a cross-sectional descriptive observational study. Information from 47 urban-industrial workers from lamps manufacturing in São Paulo, clinically diagnosed as intoxicated by mercury and currently followed by the Occupational Health Service of Faculdade de Medicine da Universidade de São Paulo, with average age of 41.7 years old, was considered. Methods: SF36 questionnaire application was performed, with inferences tested by χ-square proof, by Spearman linear correlation and Mann-Whitney non-parametric test, adopting p < 0.05 as significant level. Results: In the eight domains, observed medians are 40% for physical functioning; 0 for physical function; 30% for body pain; 30% for general health; 22.2% for vitality; 50% for social functioning; 0 for emotional role and 36% for mental health. Correlation between age and SF36 domains does not reveal statistical significance, except for physical functioning, indicating that lower scores presented by older people in this domain are not followed by changes on other ones. Conclusions: Values obtained in people chronically intoxicated by mercury are actually lower, in the motor and mental scope components. Some instruments domains are higher for men than for women. Older ages are inversely associated to good performance in physical function domain. © Copyright Moreira Jr. Editora. Todos os direitos reservados.
Keywords: Epidemiology; Mercury poisoning; Quality of life; mercury; adult; aging; controlled study; correlation coefficient; emotion; female; functional assessment; health status; human; industrialization; major clinical study; male; mental health; mercurialism; occupational disease; pain; perception; performance; quality of life; questionnaire; rank sum test; Short Form 36; social status; statistical analysis; urban area